2019
DOI: 10.1088/1361-6455/ab0e5e
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the rate of entangled-photon-pair interaction with metallic nanoparticles based on classical-light second-harmonic generation measurements

Abstract: Entangled-photon-pair interaction (EPPI) with matter is a key element in many suggested quantum-light applications and an enhancement of this interaction is of great importance. In this paper, we suggest and investigate the use of metallic nanoparticles (MNPs), with their exceptional capability of light-matter coupling at their localized surface plasmon resonance, for a potential enhancement of EPPI. We specifically investigate second-harmonic generation and theoretically estimate the rate of EPPI with MNPs us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…There are other publications in this field that support our findings. In particular, Ashkenazy et al [46], argued that using "typical" values of A e (50 µm 2 ) and T e (50 fs), they can estimate σ E ≈ 10 −29 cm 2 for metallic nanoparticles with a large σ C ≈ 100 GM. Cross-sections of this size are in agreement with our established bounds of σ E .…”
Section: Resultsmentioning
confidence: 99%
“…There are other publications in this field that support our findings. In particular, Ashkenazy et al [46], argued that using "typical" values of A e (50 µm 2 ) and T e (50 fs), they can estimate σ E ≈ 10 −29 cm 2 for metallic nanoparticles with a large σ C ≈ 100 GM. Cross-sections of this size are in agreement with our established bounds of σ E .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, however, a number of studies have reported conflicting results which cast doubt on the large enhancements claimed in those reports. [15][16][17][18][19] For example, three different groups employed E2PEF measurements to determine the σ E2PA of Rhodamine 6G (Rh6G). 4,20,21 Tabakaev et al 20 measured E2PEF using CW SPDC excitation at 1064 nm with up to 5 × 10 8 pairs/sec.…”
Section: Introductionmentioning
confidence: 99%
“…In [22], Ashkenazy et al have proposed a different approach, a RFHRS method, in which the NPs are modeled as dipoles oscillating at the SH frequency, and the G-factor (for setups in which the SH signal is collected in reflection or transmission) is approximated as:…”
Section: A Shg In Nps and The Rfhrs Methodsmentioning
confidence: 99%
“…These SNPs were embedded in polyvinyl-alcohol (PVA), making it the first report of RFHRS measurements on NPs embedded in a homogenous media and not in a solution. Moreover, unlike previous experimental setups [21,22] in which the transmitted second-harmonic (SH) signal was 2 > REPLACE THIS LINE WITH YOUR MANUSCRIPT ID NUMBER (DOUBLE-CLICK HERE TO EDIT) < measured, in our implementation the SH signal was measured in reflection.…”
Section: Introduction Nergy-time Entangled-photon Pairsmentioning
confidence: 97%
See 1 more Smart Citation